Geochemical multielement signatures of glacial and interglacial facies of the Okhotsk Sea deepwater sediments during the past 350 kyr: A response to global climate changes at the orbital and millennial scales. (26th March 2015) - Chebykin, Eugene P.; Gorbarenko, Sergey A.; Stepanova, Ol'ga G.; Panov, Vsevolod S.; Goldberg, Evgeny L.
Abstract The previously dated deepwater sediment core MR06‐04 PC‐7R (length 1723 cm; 350 kyr) recovered from the central Okhotsk Sea (OS) was analyzed for biogenic compounds and for 63 chemical elements (using the inductively coupled plasma–mass spectrometry method) with a high resolution (1 cm; 200 years). A one box model with two main members" and mathematical methods (based on multielemental composition of sediments) for the calculation of weight fractions (at each time slice) of two main types of geochemical facies that dominate during considerably diverse climatic periods (glacial maxima and interglacial optima) were proposed and tested. This model can be applied to other analogous natural systems whose sedimentation is driven by two main types of geochemical facies. The application of the developed model to the studied core revealed that variations of weight fractions of the typical interglacial and glacial geochemical facies in the sediments along the core depth (named as warm and cold "covariators, " respectively) change synchronously with global and regional climate variability. Profiles of warm and inversed cold covariators coincide tightly, and their values increase during warm marine isotope stages and substages and decrease during cold ones over the last 350 kyr. Millennial scale changes in covariators had occurred simultaneously with abrupt variability in the OS productivity and sediment lithology and with millennial global climate variability. Some discrepancies in the warm and inversed cold covariators calculated using specific mathematical treatments revealed the episodic influence of volcanogenic matter presented in the core by visible tephra layers and cryptotephras.